Development of STEM-PjBL Based E-Modules Assisted by Google Sites on Solar System Material in Grade VI Elementary School - Sara Yuliasari; Risda Amini (Postgraduate, University of Mataram, 2026)
This study aims to develop and test the feasibility of a STEM-Project Based Learning (STEM-PjBL) e-module on the Solar System material for sixth-grade elementary school students. The study used the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Product feasibility was reviewed from the aspects of validity, practicality, and effectiveness. The validity test was conducted by media experts, linguists, and material experts. The validation results showed that the e-module was in the very valid category, with a validity percentage of 88% for media experts, 97% for language experts, and 95% for material experts. The practicality of the e-module was assessed through a questionnaire of teacher and student responses in two elementary schools. The results of the practicality test showed a very positive response with a very practical category, both from teachers and students. The effectiveness of the e-module was analyzed based on the improvement in learning outcomes using the N-Gain score. The results showed an increase in understanding of the solar system concept, with an N-Gain value of 0.69 (medium category) and 0.77 (high category). These findings indicate that the STEM-PjBL-based e-module is effective in improving student learning outcomes and conceptual understanding. Therefore, the developed e-module is suitable for use as an innovative and contextual science learning medium in elementary schools.